Curbing publicly-funded family planning services in Iran: who is affected?. Issue 1 (22nd December 2016) - Erfani, Amir
Abstract : Objective: In response to a persistent low fertility rate in the country, the Supreme Leader of Iran in 2012 called for the shift to pronatalist population policies. Consequently, Iran's Parliament proposed a bill to curb the provision of contraceptive knowledge and services as a solution to raising the country's low fertility rate. This study aimed to investigate which groups of women will be adversely affected if the provision of subsidised contraceptive methods [i.e. sterilisation, intrauterine device (IUD) and injections] is curbed. Methods: This study used recent data from the 2014 Tehran Survey of Fertility ( n =3012) conducted among a representative sample of 3012 married women of reproductive age, and used multinomial logistic regression analysis to identify women with a higher likelihood of using government-funded contraceptive methods. Results: Currently 82% of married women living in Tehran use a contraceptive method. The use of long-acting contraception, namely sterilisation and IUDs, declined from 34% in 2000 to 20% in 2014, and the prevalence of male methods (withdrawal and condoms) increased from 33% to 55% in the same period. Multivariate results showed that women who have a large number of children, want no more children, live in poor districts, and have low education are more likely to use long-acting contraceptive methods than withdrawal and condoms. Conclusions: Women of low socioeconomic status who want to stop childbearing are the most vulnerable subgroups of the population if the publicly-funded family planning services are curbed.